Driving sustainability in tea farming: insights on organo-mineral fertilizers - Mjanja, Braison E.; Shitindi, Mawazo J; Massawe, Boniface Hussein; Mulashani, Glory R. (Frontiers in Soil Science, 2025)
Tea (Camellia sinensis L. O. Kuntze) is a globally important crop, yet its sustainability is threatened by nutrient depletion, acidic soils, and heavy reliance on synthetic fertilizers. Prolonged use of nitrogen-based inputs has intensified soil acidification, reduced microbial diversity, increased greenhouse gas emissions, and compromised tea quality. While organic fertilizers improve soil health, their low nutrient concentrations and slow-release limit effectiveness in intensive systems. Organo-mineral fertilizers (OMFs), which blend organic matter (compost, manure, biochar) with inorganic nutrients (N, P, K), offer a balanced solution. By combining fast- and slow-release nutrient pools, OMFs enhance soil structure, increase cation exchange capacity, improve water retention, and support beneficial microbial activity. Evidence indicates they can lower nitrogen leaching and phosphorus fixation, buffer soil acidity, and maintain consistent leaf flushing, essential for yield stability in rainfed tea systems. Field trials in Asia and Africa demonstrate superior yields, nutrient uptake, and tea quality compared to synthetic fertilizers alone. However, adoption in Africa remains limited due to knowledge gaps and policy constraints. This review highlights the potential of OMFs to transform tea cultivation into a more resilient, productive, and environmentally sustainable system.